Individual and mixtures of PFAS during pregnancy are associated with maternal cardiometabolic outcomes during pregnancy - Clark R. Sims; Neha Sehgal; Donald Turner; Lauren A. Havens; Andrew J. Morris; Kartik Shankar; Kevin J. Pearson; Todd M. Everson; Aline Andres (Environmental Health)
Abstract Introduction Per- and polyfluoroalkyl substances (PFAS) are endocrine-disrupting chemicals and widespread environmental contaminants. PFAS cross the placental barrier and reach the developing fetus with potential impacts on many organ systems. There are no studies of PFAS in residents of central Arkansas despite reports of environmental contamination in the region. We aimed to quantify PFAS concentrations in repeated serum samples from participants living in central Arkansas and to investigate relationships with maternal cardiometabolic health during pregnancy. Methods Participants were enrolled during early pregnancy in a longitudinal study (NCT01131117) from 2010 to 2014. PFAS concentrations were measured in serum from each trimester (first trimester n = 282, second trimester n = 217, and third trimester n = 195). PFAS were compared across pregnancy. Linear and linear-mixed effects models were used to investigate relationships between trimester-specific PFAS levels, as single exposures, and maternal outcomes. Effects of PFAS as an exposure mixture were estimated using quantile g-computation. Results Six PFAS were detected in more than 70% of the maternal serum samples: PFOS, PFOA, PFBS, PFHxS, PFNA, and PFHxA. In adjusted linear-mixed models and quantile g-computation models, maternal serum PFAS levels were significantly negatively associated with triglycerides [effect estimates (β)= -16.29; 95% confidence interval (CI)= -24.95, -7.63], total cholesterol (β= -12.77; 95%CI= -19.80, -5.74), low-density lipoproteins (β= -10.83; 95%CI = -16.72, -4.93), high-density lipoproteins (β= -4.10; 95%CI= -6.23, -1.96), and pulse (β= -1.60; 95%CI= -2.85, -0.35). Maternal serum PFAS, as a mixture, was not associated with maternal diastolic blood pressure, but separately, PFASsum, PFOS, PFOA and PFNA had significant positive associations. Conclusion This study evaluated PFAS exposures during pregnancy in central Arkansas. We show that PFAS exposure during pregnancy influences maternal cardiometabolic outcomes and a case in point that future studies are needed to determine the impact on maternal health and to investigate potential interventions to limit the effects of PFAS exposure during pregnancy.